The governance of non-profit micro finance institutions: lessons from history - Roy Mersland (Journal of Management & Governance, 2011)
Microfinance is high on the public agenda and better corporate governance has been identified as a need to enhance the viability of the industry. Guided by stakeholder and agency theories the paper makes use of an historical parallel found in savings banks in order to present corporate governance lessons for today's microbanks. The findings indicate that monitoring by bank associations, depositors, donors and local communities were important in securing the survival of the savings banks. The willingness to expand their mission to server wealthier customers alongside the poor helped the banks to become financially viable. These findings could prompt a rethink of microfinance governance, in which regulation and traditional vertical board control are stressed. The paper argues that a broader and more stakeholder-based understanding of corporate governance is necessary.
Keywords: 650